186k views
0 votes
Solve the following absolute value equation for the unknown. Show all of your work for full credit. |-3h – 6| ≤ 3

User Sasankad
by
4.2k points

1 Answer

4 votes

Answer:


-3 \le h \le 1.

Explanation:

Apply the property of absolute values: if
a \ge 0, then
|x| \le a \iff -a \le x \le a. By this property,
|- 3\, h - 6 | \le 3 is equivalent to
-3 \le -3\, h - 6\le 3. That's the same as saying that
-3\, h - 6 \ge -3 and
-3\, h - 6 \le 3.

Add
6 to both sides of both inequalities:


-3\, h \ge 3 and
-3\, h \le 9.

Divide both sides of both inequalities by
(-3). Note that because
-3 < 0, dividing both sides of an equality by this number will flip the direction of the inequality sign.


  • -3\, h \ge 3 would become
    h \le -1.

  • -3\, h \le 9 would become
    h \ge -3.

Both inequalities are supposed to be true. Combining the two inequalities to obtain:


-3 \le h \le 1.

User SomeWritesReserved
by
4.4k points